Comparison of lifing results of gas turbine operated in base load and as a back up to wind turbine - Mohamed, Saleh; Ali, Ezeddin; Pilidis, Pericles; Sampath, Suresh (IJRES, 2019)
When operating the gas turbine in a flexible mode as a back up to renewable energy sources such as wind, solar, tidal and so on. A fluctuation of power produced by the GT will be apparent which in turn will cause low cycle fatigue in the high-pressure turbine blades. The drive behind this study is to estimate the life of a 100 MW GT operated in a baseload scenario and compare the lifing results with two different scenarios of operating the GT as a back up to a wind turbine operated in the UK in 2016. For the estimation of the GT lifing, some performance parameters are essential such as turbine entry temperature (TET), blade cooling temperature (Tc), and the shaft rotational speed (PCN). All these parameters are obtained from running the in-house TURBOMATCH model, which was developed in Cranfield University, under certain operating conditions (temperature and pressure). These values are used with other parameters as input to a FORTRAN code to estimate the lifing and lifing consumption of the GT. In comparison, it was found that the base load scenario has the highest value of creep while in the backup scenarios the LCF was higher due to the power fluctuation.
Keywords: Gas Turbines; Flexibility; Wind Energy; Creep; Fatigue; Lifting